2005
DOI: 10.3168/jds.s0022-0302(05)72858-7
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptability of Conjugated Linoleic Acid-Enriched Milk and Cheddar Cheese from Cows Grazing on Pasture

Abstract: Two experiments were conducted to study the consumer acceptability attributes of conjugated linoleic acid (CLA)-enriched milk and cheese from cows grazing on pasture. In experiment 1, 15 cows were fed either a diet containing 51% alfalfa hay plus corn silage and 49% concentrate [total mixed ration (TMR)], were grazed on pasture, or were grazed on pasture and received 3.2 kg/d of a grain mix. The grain mix contained 75% full-fat extruded soybeans (FFES), 10% corn, 10% beet pulp, and 5% molasses. During the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 33 publications
1
46
1
3
Order By: Relevance
“…As in our study, Khanal et al (2005) did not found effects of a mixed supplement containing 2.4 kg d -1 of extruded soybean on CLA concentration in the milk of Holstein cows on pasture (1.63 and 1.69% of total FA for groups fed on pasture alone and pasture + supplement mixed with extruded soybean, respectively; these values include the cis-9, trans-11 isomer). The values obtained by these authors are somewhat higher than those found herein for the three CLA isomers together.…”
Section: Cla Content and Compositionsupporting
confidence: 53%
See 2 more Smart Citations
“…As in our study, Khanal et al (2005) did not found effects of a mixed supplement containing 2.4 kg d -1 of extruded soybean on CLA concentration in the milk of Holstein cows on pasture (1.63 and 1.69% of total FA for groups fed on pasture alone and pasture + supplement mixed with extruded soybean, respectively; these values include the cis-9, trans-11 isomer). The values obtained by these authors are somewhat higher than those found herein for the three CLA isomers together.…”
Section: Cla Content and Compositionsupporting
confidence: 53%
“…However, contradictory results has been found on the effects of soybean supplementation and CLA content in milk on feeding systems based on fresh forage. Some studies (Bartolozzo et al, 2003;Khanal et al, 2005) did not found effects on milk CLA concentration in dairy cows, while others (Lawless et al, 1998;Paradis et al, 2008) observed an increase in the CLA using dairy and beef cattle.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Differences between diets CS and RB are not easy to explain since intakes of precursors of these two FA in milk were similar. Some authors suggest that whole seeds may produce a lower concentration of TVA and RU in milk lipid than processed seed, due to a lower ruminal availability of unsaturated FA in whole seeds, where FA are protected from ruminal biohydrogenation, resulting in a higher concentration of milk unsaturated FA (Dhiman et al, 2000;Khanal et al, 2005;Paradis et al, 2008). However, CS had lower concentrations of LI and LN acids and higher concentrations of stearic acid in milk lipids than RB, suggesting a more extensive biohydrogenation in the CS diet.…”
Section: Discussionmentioning
confidence: 99%
“…The content of CLA in fat from ruminant-derived foods is dependent on the ruminal production of both CLA, trans-vaccenic acid (TVA), and on the tissue activity of Δ 9 -desaturase. For instance, it has been reported that fresh forage (Khanal et al, 2005;Dewhurst et al, 2006;Butler et al, 2008; Conjugated linoleic acid content in milk of Chilean Black Friesian cows under pasture conditions and supplemented with canola seed (Brassica napus) concentrate Rego et al, 2008) and diets supplemented with plant oils, high in linoleic acid Stanton et al, 2003) increase CLA concentration in milk fat. Within the seeds of oilseeds, rapeseed (Brassica napus) has been used in TMR (total mixed ration) diets in dairy cows (Bayourthe et al, 2000, Chouinard et al, 2001Ward et al, 2002;Chichlowski et al, 2005;Chen et al, 2008;Neves et al, 2009;Lerch et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%